A Comparative Study Between Mri And Transcranial Usg In Etiological Diagnosis Of Neonatal Seizure - Sinha, Trisha; Maji, Soumit; Karim, Rezaul (Journal of Neonatal Surgery, 2025)
Background: Neonatal seizures are critical neurological emergencies and often signal underlying central nervous system abnormalities. Prompt identification of the etiology is vital for prognosis and treatment. While Magnetic Resonance Imaging (MRI) is the gold standard for neonatal neuroimaging, Transcranial Ultrasonography (TUS) is widely used due to its bedside availability and cost-effectiveness. This study aims to compare MRI and TUS in diagnosing the etiology of neonatal seizures. Methods: A cross-sectional analytical study was conducted on 60 neonates presenting with seizures at MGM Medical College & LSK Hospital, Kishanganj, Bihar. Each neonate underwent both MRI and TUS. Imaging findings were correlated with clinical outcomes. Diagnostic metrics such as sensitivity, specificity, predictive values, and ROC curves were calculated. Results: MRI showed superior sensitivity (93.3%) and specificity (90.0%) compared to TUS (55.0% and 80.0%, respectively). MRI detected more cases of hypoxic-ischemic encephalopathy (90.9% vs. 54.5%), intracranial hemorrhage (100% vs. 83.3%), metabolic encephalopathy (71.4% vs. 28.6%), infections (100% vs. 50%), cerebral infarcts (100% vs. 50%), and congenital malformations (100% vs. 40%). MRI had a higher overall diagnostic accuracy (91.7%) compared to TUS (65.0%). MRI findings were more predictive of neurodevelopmental outcomes. Conclusion: MRI remains the superior modality in etiological diagnosis of neonatal seizures, demonstrating significantly higher diagnostic performance and predictive value compared to TUS. However, TUS retains value as a preliminary screening tool, particularly in resource-limited settings.